Framing Analysis of Indonesian Fast Train on detik.com - Susilo, Daniel; Harliantara, Harliantara (Gema Kampus IISIP YAPIS Biak, 2023)
Fast Train is a train that is currently the main focus of Indonesian citizens because it involves big names from officials like Luhut Binsar Pandjaitan. Several times his figure has resulted in heated discussions about fast trains and criticism for the country. Indonesia joins the fast train Together with China, which made an agreement with Indonesia to build fast train infrastructure and the results are still ongoing today. Detik.com as a media provider of news services provides news about fast trains, some of the data found also found positive indications from Detik.com for good news about fast trains. With framing analysis we can find out what the true meaning is behind the positive high-speed train news.